2011
DOI: 10.1007/s11440-011-0146-3
|View full text |Cite
|
Sign up to set email alerts
|

3D-electrical resistivity tomography monitoring of salt transport in homogeneous and layered soil samples

Abstract: Monitoring transport of dissolved substances in soil deposits is particularly relevant where safety is concerned, as in the case of geo-environmental barriers. Geophysical methods are very appealing, since they cover a wide domain, localising possible preferential flow paths and providing reliable links between geophysical quantities and hydrological variables. This paper describes a 3D laboratory application of electrical resistivity tomography (ERT) used to monitor solute transport processes. Dissolution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated the feasibility of EIT to qualitatively image unsaturated moisture flows in porous media. Such research includes: 1D and 2D unsaturated moisture flow in soil [38,39,40,41] and cement-based material [42,43,37,15], as well as 3D moisture flow in sand [44], sandstone [45], soil [46] and cement-based materials [36]. In all these works, (the spatial map of) the increase of the moisture content with respect to some initial state was inferred qualitatively x, y, z spatial coordinates from a relative increase in the electrical conductivity (or decrease in the electrical resistivity) distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the feasibility of EIT to qualitatively image unsaturated moisture flows in porous media. Such research includes: 1D and 2D unsaturated moisture flow in soil [38,39,40,41] and cement-based material [42,43,37,15], as well as 3D moisture flow in sand [44], sandstone [45], soil [46] and cement-based materials [36]. In all these works, (the spatial map of) the increase of the moisture content with respect to some initial state was inferred qualitatively x, y, z spatial coordinates from a relative increase in the electrical conductivity (or decrease in the electrical resistivity) distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The reconstructed electrical conductivity field is then obtained. ERT has been successfully used to detect heterogeneities [9], or to visualize mechanical and transport processes in soil samples [10], also allowing estimating the water retention and hydraulic properties of different soils [11]. It also has been fruitfully used to investigate moisture movement in cement, both undamaged [12] -thus allowing to study the homogeneous behaviour of the material matrix -and cracked [13].…”
Section: Electrical Resistivity Tomographymentioning
confidence: 99%
“…There is a broad range of applications of EIT to many settings, including the detection of bodily tumors, damaged industrial materials, and oil reservoirs to mention a few. More specifically, EIT has been applied in some of the following applications: noninvasive medical imaging [7,64], nondestructive testing [26], monitoring of oil and gas mixtures in oil pipelines [47], and monitoring the water infiltration in soil [13,23,25,26]. However, along with its ease of use comes the difficulty in recovering resolvable and reliable tomographic images.…”
Section: Introductionmentioning
confidence: 99%